LSS-based business systems analysis a case study of a billing system for contracted services - Ramirez, Leilani Ramos; Rañeses, Nestor O. (Quezon City University of the Philippines Diliman, 2014)
Speed. Quality. Low Cost. Quantity. George (2003) emphasized that these universal goals, with the inclusion of quantity which is an equally important criteria for Services industry, have been around as long as there has been competition in business. Many separate disciplines have evolved to achieve these goals, however, only Lean Six Sigma (LSS) will let you work on all four simultaneously because it blends Lean, with its primary focus on process speed, and Six Sigma, with its primary focus on process quality. The end result will attain all four objectives and total customer satisfaction. An attractive Employee Reduction Program offered to Company X's tenured employees reduced the total workforce by more than 50 percent since its implementation 18 years ago. The continuous manpower reduction program and the company's synergy strategy with its growing group of companies led significant changes in its value chain activities to ensure its competitiveness and leadership in the industry. Foremost is the outsourcing of several primary and support activities in the value chain to 3rd party vendors. One major hurdle encountered is how to bill for the services rendered and safeguard the company's image to their valued customers with 3rd party vendors in the frontline. To alleviate this problem, the company started automating the existing manual processes and embarked on digital technology to minimize manpower dependency in its operations; however, the lack of the right tools and methodologies for an effective problem solving technique led to automating non-value adding activities resulting to defects, unintended variation, rework, additional people and technology resources, and customer dissatisfaction. This study aims to apply a Lean Six Sigma-based approach to business analysis processes in Services-particularly on Company X's billing system for contracted services. Rooted from a previous billing automation requirement to fast track processing of payments to 3rd party vendors, the use of LSS methodologies intends to achieve business process excellence by improving quality, eliminating waste, reducing lead time and reducing total costs. Pyzdek (2003) defines quality as a measure of value added by a productive endeavor. Potential quality is the maximum possible value added per unit. Actual quality is the current value added per unit of input. The difference between potential and actual quality is "muda" or waste. One of the central tenets of Lean Six Sigma, according to George (2003), is that unnecessary complexities in a process add costs, time and enormous wastes. And one of the major challenges in applying Lean to a service environment is calling something that's accepted as "just the way work happens" by a new name : waste. Similarly, Longo (n.d.), states that in order to achieve operational excellence, one has to develop the ability (1) to recognize and identify waste; (2) to have the courage to call it waste; (3) to have the desire to eliminate it; and (4) eliminate the waste. Learning to recognize wastes and the willingness to shift paradigm of how things are normally done guarantee Company X the benefits of Lean Six Sigma - speed, quality, low cost and quantity.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Business -- Computer programs; Business -- Management